SISTEM PERINGATAN DINI UNTUK MENDETEKSI KETERLAMBATAN PEMBAYARAN KREDIT BANK - Novita, Rice (Jurnal Teknik Elektro, 2014)
PT. Bank Perkreditan Tuah Negeri Mandiri is a bank conducting business in a conventional or based on Shariah principles in its activities do not provide services in payment traffic . The main activity of BPR is intended to serve small businesses and communities in rural areas . One key to success is a credit monitoring . The number of bad credit or no credit unpaid in part or in whole is very influential on the development of the Bank . Application Development Early Warning System to detect late payment of credit is helpful in monitoring the Bank . Application Early Warning System will issue a message box to debtors who entered the payment due credit . Early Warning System type used in the form of database alerts . Message box is issued based on the existing data in the database . This early warning system also serves to perform the data processing of credit and also displays a graph of the number of debtors in each districts in the area of Pekanbaru .